Comfort Simulator: A Software Tool to Model Thermoregulation and Perception of Comfort. Issue 1 (20th July 2020) - Hussan, Jagir R.; Hunter, Peter J.
Thermophsyiological comfort is critical to well-being and optimal productivity of humans. Environmental changes, modern materials and novel occupational settings necessitate evaluation of their impact on comfort and inform both product design and occupational health. We present an open-source research software tool to simulate thermophysiological comfort for different human geometries, body-constitution conditions, clothing, ambient temperature, humidity and radiative heat flux conditions. The tool, developed using python, integrates a diverse set of models. The components that code the models can be easily replaced and the simulation pipeline can be executed with minimal disruption.